Implementation of Literacy and Qur’anic Recitation Programs in Improving the Quality of Education and Children’s Character in Selemak Hamparan Perak Village - Nadira Ayu Putri Sikumbang (Yayasan Rahmat Islamiyah, 2026)
Literacy and Qur’anic recitation programs are strategic efforts to improve educational quality while fostering children’s character from an early age. These programs aim to develop reading and writing skills as well as to instill Islamic values oriented toward noble character formation. This study aims to analyze the implementation of literacy and Qur’anic recitation programs in improving the quality of education and children’s character in Selemak Hamparan Perak Village. A qualitative approach with a descriptive design was employed, using observation, interviews, and documentation as data collection techniques. The research subjects included children, program facilitators, and local community leaders. The findings indicate that the implementation of literacy and Qur’anic recitation programs has a positive impact on improving children’s reading and writing abilities, basic religious understanding, and behavioral changes reflecting discipline, responsibility, and religiosity. Furthermore, the program contributes to increasing children’s learning motivation and fostering a love for worship activities. Therefore, literacy and Qur’anic recitation programs can serve as a sustainable community-based model for educational and character development.